2021
DOI: 10.3389/fimmu.2021.609700
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of the Gut Microbiome in Chronic Kidney Disease Patients and Its Association With Serum Free Immunoglobulin Light Chains

Abstract: ObjectivesGut dysbiosis is associated with chronic kidney disease (CKD), and serum free immunoglobulin light chains (FLCs) are biomarkers for CKD. This study aims to assess the CKD gut microbiome and to determine its impact on serum FLC levels.MethodsTo control for confounders, 100 patients and sex- and age-matched healthy controls (HCs) were recruited. The gut microbiome was assessed by sequencing 16S rRNA gene V3-V4 hypervariable regions. Phylogenetic Investigation of Communities by Reconstruction of Unobser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 52 publications
5
27
1
Order By: Relevance
“…The CKD patients with normal or high eGFR, moderate CKD, and end-stage CKD displayed a different fungal community with respect to healthy subjects, whereas the patients with mild CKD and severe CKD did not exhibit a difference from that in the HC cohort. These findings also appeared in our previous study on the bacterial microbiome in CKD patients ( 3 ). The restoring process that appeared in patients, including the fungal and bacterial microbiome, should be examined using animal models.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The CKD patients with normal or high eGFR, moderate CKD, and end-stage CKD displayed a different fungal community with respect to healthy subjects, whereas the patients with mild CKD and severe CKD did not exhibit a difference from that in the HC cohort. These findings also appeared in our previous study on the bacterial microbiome in CKD patients ( 3 ). The restoring process that appeared in patients, including the fungal and bacterial microbiome, should be examined using animal models.…”
Section: Discussionsupporting
confidence: 85%
“…As sex, age, and BMI are important variables affecting the gut microbiome ( 23 25 ), we recruited ninety-two CKD patients and sex–age–BMI–matched healthy controls (HCs) were recruited from December 2018 to February 2020. The inclusion and exclusion criteria were based on our recent study on the bacterial microbiome in CKD patients ( 3 ). The diagnostic criteria for CKD include a decreased eGFR [<60 ml/min/1.73 m 2 ) or an evidence of kidney damage such as albuminuria (albumin excretion rate ≥30 mg/24 h; urinary albumin– creatinine ratio (UACR) ≥30 mg/g], urine sediment abnormalities, electrolytes, and other abnormalities due to tubular disorders, abnormalities detected by histology, and structural abnormalities detected by the imaging or history of kidney transplantation ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduced abundances in unidentified Melainabacteria, family of the unidentified Melainabacteria and Prevotellaceae , and the unidentified genus Melainabacteria suggest that those bacteria are susceptible to the administration of 6-MBOA, which verifies the antimicrobial properties of 6-MBOA ( Wang et al, 2001 ; Wang and Ng, 2002 ; Martyniuk et al, 2006 ). Chloroalkane and chloroalkene degradation, a pathway also involved in xenobiotic biodegradation and metabolism ( Liu F. et al, 2021 ), was consistently observed to be dose-dependently improved by 6-MBOA administration in cecal microbiota of Brandt’s voles.…”
Section: Discussionmentioning
confidence: 99%